An Analysis of Multiple Size Region of Interest in Disparity Mapping for Stereo Vision Application - Hamzah, Rostam Affendi; Hamid, Mohd Saad; Rosly, Hasrul Nisyam (2011)
This paper presents an analysis of multiple size region of interest in selected area or segment of disparity mapping in application of stereo vision.